ANALISIS OIL LOSSES PADA STASIUN PRESS DALAM PENGOLAHAN CPO (CRUDE PALM OIL) DENGAN METODE STATISTICAL PROCESS CONTROL (SPC) DI PT PERKEBUNAN NUSANTARA III PKS RAMBUTAN TEBING TINGGI SUMATERA UTARA - Desniorita Desniorita; Eliza Eliza (JURNAL ILMIAH TEKNOLOGI INDSUTRI (SAINTI), 2019)
Crude Palm Oil (CPO) is obtained from the extraction process from palm fruit pulp. The extraction process is carried out at the press station. The working principle at the press station is to press the palm raw material in a hollow tube with a rotating screw so that oil will come out through the holes of the tube. The amount of pressure this tool can be adjusted electrically and depends on the volume of material being pressed. This tool consists of a cylinder with a hole in the inside there is a rotating screw. Press pressure is regulated by two cones (conus) located at both ends of the press, which can be driven back and forth hydraulically. Hydraulic pressure at 50-70 kg / cm3 commulator results in wet pulp, resulting in oil losses. The purpose of this study was to determine whether oil losses occurred at the press station in producing crude palm oil (CPO) at PT Perkebunan Nusantara III PKS Rambutan in Tebing Tinggi, North Sumatra by using the Statistical Process Control method. From the research, it is known that from the results of statistical process control (SPC) analysis, it is known that the level of achievement of standards expected by the company has not been achieved on fiber pulp. Where the results of the examination on the fiber pulp sample there are still quality factors that are outside the quality requirements or deviations occur. From the results obtained, it is necessary to propose improvements in performance, both from the quality of humans, machinery and raw materials for CPO processing.